ANALISIS KESESUAIAN LAHAN TANAMAN AGROFORESTRY DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) UNIVERSITAS LAMBUNG MANGKURAT - Yamani, Ahmad; Rudy, Gusti Seransyah; Agustina R., Arfa; Radam, Rosidah R. (Lambung Mangkurat University-Indonesia, 2025)
The failure of forest and land rehabilitation activities has often been attributed to fires; however, this is not always the case. It may also be due to the recommended plant species being unsuitable for the habitat or lacking a scientific basis. To ensure the success of forest and land rehabilitation activities and achieve their goals, the paradigm must shift. Specifically, the selection or recommendation of plant species should align with the characteristics of the land and involve local communities, as such initiatives often fail without their participation. For this reason, an agroforestry system—rehabilitating forest areas by planting forestry and agricultural crops with local farmers—needs to be implemented. This study aims to analyze the land suitability classes for Candlenut (Aleurites moluccana WILLD) and Corn (Zea mays) as agroforestry crops in the Special Purpose Forest Area (KHDTK) of Lambung Mangkurat University. The significance of this research lies in providing solutions to prevent forest and land fires while addressing critical land issues in KHDTK ULM. In principle, land suitability classification is conducted by integrating the plant's growth requirements with the land's characteristics. Hence, this classification is often referred to as the